An unconventional approach to evaluate the Bank of England's asset purchase program - Matthias Neuenkirch (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2016)
Empirical papers analysing the transmission of (unconventional) monetary policy typically rely on a vector autoregressive framework. In this paper, I complement these studies and employ a matching approach to examine the impact of the Bank of England's asset purchase program on macroeconomic quantities in the UK. My sample covers the period March 2001 - December 2015 and five small open inflation targeting economies. Using entropy balancing, I create a synthetic control group comprised of credible counterfactuals for the sample of observations subject to the asset purchase program. My key results are that a 100 bn GBP increase in asset purchases has a significant and positive effect on GDP growth with a peak effect of 0.66 - 0.69 percentage points (pp) after 30 months. The same increase leads to a reduction in the inflation gap with a peak effect between -0.77 and -0.94 pp after 30 months. An in-depth analysis reveals that the latter finding is not driven by the choice of the empirical methodology. In contrast, I find that the returns on asset purchases are decreasing (i) over time and (ii) with the level of asset purchases. This causes the impact of asset purchases on the inflation gap to eventually become negative.
Keywords: E52; E58; 330; Asset Purchases; Bank of England; Entropy Balancing; Matching; Quantitative Easing; Treatment Effects; Unconventional Monetary Policy